Oncological Outcomes in Patients with Appendicular Myxofibrosarcomas: A Retrospective Study. (28th November 2021) - Lee, Yonghoon; Guertin, Michael P.; Summers, Spencer; Conway, Sheila A.; Al Maaieh, Mothasem; Yechieli, Raphael; Trent, Jonathan; Rosenberg, Andrew E.; Pretell-Mazzini, Juan
Abstract : Background . Myxofibrosarcoma (MFS) is notorious for its infiltrative growth pattern, making wide excisions difficult to achieve. Our objective was to assess the impact of surgical margins and other factors that affected rates of local recurrence (LR), distant metastasis (DM), and overall survival (OS) of individuals undergoing resection for MFS. Methods . We retrospectively reviewed the medical records of 209 patients with appendicular soft tissue sarcomas between January 2012 and June 2018. Of these, 29 patients (14%) were diagnosed with myxofibrosarcoma. These patients underwent a total of 33 resections. The pathological analyses were conducted by an experienced musculoskeletal (MSK) pathologist. Demographics data, operative details, adjuvant therapy, and oncological outcomes were assessed. Results . Of the 29 patients (33 resections), the overall LR rate was 24% (7/29) and the 2-year LR rate was 17% (5/29). Factors associated with negative oncological outcomes were as follows: tumor size ≤10 cm (2-year local recurrence-free rates (LRFRs), 65%; 95% CI, 44–86%; p = 0.02 ) and positive surgical margins grouped with surgical margins ≤0.1 cm (hazard ratio (HR), 11.74; 95% CI, 1.41–97.74; p = 0.02 ). Chemotherapy and radiotherapy together increased the 2-year LRFR (LRFR, 100%; 95% CI, 100%, p = 0.001 ). Two-year DM and OS rates were 15% and 79%, respectively. Female gender was a predictor of distant metastasis. Local recurrence had a negative impact on overall survival. Intraoperative analysis of resection margin accuracy was 75% (12/16) when non-MSK pathologists were involved but 100% accurate (12/12) when analyzed by an MSK pathologist. Conclusion . Myxofibrosarcomas showed high LR rates after treatment. Close margins (≤0.1 cm) should be considered as a risk factor for LR, and LR is associated with negative overall survival. Neoadjuvant therapy in terms of combined chemotherapy and radiation therapy associates with decreased LR rates. If intraoperative assessment of margins is to be done, it should be performed by an experienced MSK pathologist.